Correction: Robust electrochemical metal oxide deposition using an electrode with a superhydrophobic surface. Issue 15 (6th April 2017) - Zhang, Jun; Sheng, Xia; Cheng, Xiqing; Chen, Liping; Jin, Jian; Feng, Xinjian
Abstract : Correction for 'Robust electrochemical metal oxide deposition using an electrode with a superhydrophobic surface' by Jun Zhang, et al., Nanoscale, 2017, 9, 87–90.